The Role Activity of Complement, TNFα & IL12 in Pathogenesis Dengue Virus - Soegijanto, Soegeng; Sary, Dian Dwi; Setiawan, Budi; Yamanaka, Atsushi (Indonesian Journal of Tropical and Infectious Disease, 2010)
Dengue Virus infection is always found in some part of the world especially South East Asia including Indonesia. The pathogenesis of Dengue Virus infection is still controversial. The aim of this study is to analyze the role complement activity, TNFα & IL12 in Dengue Virus infection especially in pathogenesis of Dengue Virus infection. Cross sectional study had been done since February 2009 in Dr. Soetomo Hospital Surabaya. Blood Sera of Dengue Virus infection were collected from Dengue Fever, and Dengue Hemorrhagic Fever patient who had been care in Paediatric. Dengue patients and time schedule for taking blood sample for examination CH50, TNFα & IL12 as follow: on the first day on admission, the second day, the third day. Study groups of patients as follow: Dengue Fever, 36; Dengue Hemorrhagic Fever grade I, 37; Dengue Hemorrhagic Fever grade II, 10; Dengue Hemorrhagic Fever grade III, 18; Dengue Hemorrhagic Fever grade IV, 6. In this study found that the higher activity complement which lower level CH50 was more identified on Dengue Shock Syndrome and Dengue Hemorrhagic Fever grade III than Dengue Fever cases. A concept of our study was focusing on manifestation of vascular leakage, measurement of complement activity CH50, TNFα & IL12 and clinical manifestation Dengue Hemorrhagic Fever. The examination of TNFα & IL12 in our study supported the role the activity complement. The conclusion are measurement CH50, TNFα & IL12 can be used as a predictive factor of the degree of Dengue Virus infection